"Shared Destiny": The Dynamics of Relationships in Families of Patients With Brain Injury. (January 2018) - Segev, Einav; Levinger, Miriam; Hochman, Yael
This qualitative research focused on the relationships between family members of patients with acquired brain injury (ABI). The aim was to explore the dynamics between caregivers of the family member with a brain injury during rehabilitation hospitalization, and the relationships between them and the rest of the extended family. Twenty semistructured interviews were conducted with family members. In each family, the spouse of the patient and another family member involved in caregiving were interviewed. The importance of the relationships between family members during rehabilitation hospitalization justifies the examination undertaken in this research. Findings point at the change that took place in the relationships between family members because of the need to cope with a relative's injury. It is possible that direct intervention in the dynamics of the relationship, especially between the family of origin and the nuclear family of the injured person, can benefit extended families in coping with the crisis.